المشاكل البيئية الراهنة ودور الجغرافية في الحد من تفاقمها (بعض المشاكل البيئية في ليبيا نموذجا) (Journal of Humanitarian and Applied Sciences, 2023)
The environment, With its various natural and human components, suffers from many and exacerbating environmental problems, and because most of these environmental problems and issues have different geographical dimensions, as since ancient times the relationship between geography and the environment has been strong and growing, which has deepened in the recent period as a result of the modern scientific trends of geography, and this is largely done in the pursuit of Geography to contribute to defining the environmental issues that humans and society suffer from, and toplay an important role in solving these problems. Based on these data and as a contribution from us in strengthening environmental awareness locally and internationally, and showing the role of geography in solving environmental issues and protecting them and optimizing the exploitation of natural resources, and this is what this research paper aims to, in addition to providing a clear picture of natural resources and what threatens them, in order to work On reducing these risks and trying to address their negative consequences, as this study tries to answer the extent of the contributions of geography to solving environmental problems, in addition, can geographical studies indicate possible changes that may affect ecosystems? This research relies on the descriptive approach and adopting the method of extrapolation in data analysis, as it is clear that this approach aims either to monitor a specific phenomenon or topic in order to understand the general content, or its primary goal may be to evaluate a specific situation for scientific purposes. Geography has contributed to providing appropriate solutions to many modern environmental problems, especially those that the geographic envelope is exposed to, because these problems can only be solved by studying the interrelationships between the various geographical elements. The importance geography and its great role in protecting resources and rationalizing their exploitation is evident, including its role in protecting water resources, studying the relationship between the hydrosphere and the various elements of the surrounding environment, protecting the air and the resulting consequences, and developing solutions and proposals to reduce risks. That threaten the whole world.